Pioglitazone Ameliorates Atorvastatin-Induced Islet Cell Dysfunction through Activation of FFA1 in INS-1 Cells. (3rd February 2019) - Zhu, Kongbo; Qian, Linglin; Lin, Yanshan; An, Li; Mu, Guangjian; Ma, Genshan; Ren, Liqun
Abstract : Increasing evidence shows that statins increase the risk of new-onset diabetes mellitus, but the exact mechanism is not clearly known. Free fatty acid receptor 1 (FFA1) has been recognized to mediate insulin secretion, and pioglitazone has direct effects on glucose-stimulated insulin secretion in addition to the reversion of insulin resistance. In this study, we found that atorvastatin decreased potassium-stimulated insulin secretion and inhibited the expression of FFA1, PDX-1, and BETA2/NeuroD in INS-1 cells. Further study demonstrated that pioglitazone prevented the impairment of insulin secretion induced by atorvastatin and enhanced the expression of FFA1, PDX-1, and BETA2/NeuroD reduced by atorvastatin in INS-1 cells. In addition, the preventive effect of pioglitazone on atorvastatin-induced impairment of insulin secretion and the enhancement of the expression of PDX-1 and BETA2/NeuroD was abolished by knockdown of FFA1 using siRNA or the PLC inhibitor, U-73122, respectively. Ultimately, FFA1 may mediate the atorvastatin-induced pancreatic β -cell dysfunction and pioglitazone may ameliorate this deleterious effect through the upregulation of FFA1 expression.